Predicting growth and development of the pineapple cultivar ‘MD-2’ with the DSSAT Aloha Pineapple Model - Vásquez Jiménez, J. (2024)
Introduction – The Cropping Systems Model Aloha-Pineapple is a computer model that simulates pineapple growth and development and predicts final yield. The unique physiological characteristics of the cultivar ‘MD-2’ were added to the model to be more representative of the current and more common cultivars. The model has the potential to interpret fundamental processes related to crop response to environmental conditions in terms of growth and productivity. Materials and methods – Experimental data from ‘MD-2’ plants were used. The plants were grown in three environments in Costa Rica differing in temperature and solar radiation, using managed and standard agribusiness practices. Soil water and nutrients were considered non-limiting factors for growth and were uniformly controlled. Model evaluation was conducted for the prediction of phenological stage of physiological maturity using actual data from production fields of a Costa Rican pineapple ex- port company. Results and discussion – The model was improved by adding and enhancing the simulation of five vegetative and six reproductive phenological stages. Model evaluation was satisfactory based on the statistical analysis for all experiments that were conducted. Conclusion – The modeling approach allows to simulate diagnostic agronomic indicators that can assess the effect of the environment and their interaction with agronomic management on growth and development, to predict the productivity of pineapple, and to predict the harvest date for both naturally flowering fruit and for forcing.